Effects of maize cob on fish feed floatation, nutrient utilization and growth performance of African catfish (Clarias gariepinus) fingerlings (2011)
This study was carried out to determine the effects of maize cob on fish feed floation, growth performance and nutrient utilization of Clarias gariepinus fingerlings as a replacement for wheat bran. Triplicate groups of 30 fish per treatment were stocked in 3 plastic bowls each containing 15 litres of water. The initial average weight of fish was 2.43 ± 0.01. The fish were fed with 5 different test diets. The control contained 100% wheat bran (treatment 1). The wheat bran was partially replaced with 10%, 20%, 30% and 40% maize cob in treatment 2, 3, 4 and 5 respectively. The treatments were fed to each group of experimental fish at 3% body weight. The feeding trial lasted for six weeks and the growth performance were recorded weekly. There were significant differences in most of the growth performance measured. The mean weight gain of the treatment 1, 2, 3, 4 and 5 were 1.54g, 1.75g, 2.15g, 1.24g and 1.22g respectively. The fish fed treatment 3 had the highest percentage weight gain (PWG) value of 88.48% while those fed treatment 5 had the lowest value of 50.21%. The highest specific growth rate (SGR) was observed in fish fed treatment 3 (0.47), followed by treatment 2(0.33), treatment 1(0.23), treatment 4(0.15) and treatment 5(0.10) respectively. Fish fed treatment 3 had the highest protein efficiency ratio (PER) of 0.038 and the lowest was observed in treatment 5(0.026). The feed conversion ratio observed in treatment 5 was significantly higher than those fed with other treatments and the lowest was observed in treatment 3. There were significant differences in the nutrient utilization amongst the treatments at P<0.05. Treatments 1 and 3 had 20% floatability at the end of 10 minutes while treatment 2 had 10% floatability, treatment 4 and 5 had 0% floatability at the end of 10 minutes. This experiment shows that 20% inclusion level of maize cob has a greater potential as a partial replacement for wheat bran. This was because fish fed treatment 3(20% inclusion) had the highest growth parameters followed by treatment 2, treatment 1, treatment 4 and treatment 5 respectively. However fish fed treatment 3 and treatment 2 were observed to have better growth indices than the control treatment while the fish fed treatment 5 performed poorest. This further confirmed the better potential of maize cob over wheat bran which is commoner in Nigerian market.